Multidimensional Sustainability Analysis of Social Forestry Program in Mount Rakutak Protected Forest, West Java-Indonesia - Pujo, Pujo; Mulyaningrum, Mulyaningrum; Almaghfiroh, Choiruriwayancanti Fatimah; Nurhayati, Trisna; Annisa, Risky; Munawir, Abdillah (ASTONJADRO, 2026)
Social Forestry (Perhutanan Sosial) has been widely promoted in Indonesia as a dual strategy to enhance rural livelihoods while safeguarding forest ecosystems. This study assesses the sustainability of the Social Forestry Utilization Permit Scheme (IPHPS) implemented by the Mulya Tani Forest Farmer Group in Mount Rakutak Protected Forest, Bandung Regency, West Java. The RapSForest framework was employed to evaluate three dimensions of sustainability: ecological, socio-economic, and institutional. Data were obtained through household surveys (n=104), key stakeholder interviews, participatory observation, and secondary sources. Findings reveal that the overall multidimensional sustainability index is only 29.92%, classifying the program as “unsustainable” (<50%). Ecologically, the low Normalized Difference Vegetation Index (NDVI) and Shannon–Wiener diversity index (H’) indicate limited forest recovery and reduced biodiversity. Socio-economically, household incomes remain below the regional minimum wage, constrained by inadequate access to finance and weak market integration. Institutionally, deficiencies in governance, low transparency, and limited trust in leadership undermine program effectiveness. Leverage analysis highlights NDVI, H’, household income, and institutional trust as the most influential factors shaping sustainability outcomes. These results emphasize the need for multidimensional interventions: strengthening reforestation and biodiversity conservation, enhancing rural livelihoods through financial innovation and market access, and improving governance through transparency, accountability, and community participation. An integrated ecological–economic–institutional approach is essential to reconcile conservation objectives with local livelihood needs and ensure the long-term success of Indonesia’s social forestry policy.